1996
DOI: 10.1111/j.1476-5381.1996.tb15585.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the antithrombotic effect of aurintricarboxylic acid on arterial thrombosis in rats and guinea‐pigs

Abstract: . The antithrombotic effect of aurintricarboxylic acid (ATA) which inhibits binding of von Willebrand factor (vWF) to platelet glycoprotein lb (GPlb) receptor was evaluated in photochemically‐induced thrombosis models in the femoral artery of rats and guinea‐pigs. . ATA at a dose of 10 mg kg−1 significantly prolonged the time required for thrombotic occlusion of the artery in rats. The antithrombotic efficacy was associated with a significant inhibition of platelet retention and ex vivo botrocetin‐induced plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…We previously reported a simple and reproducible thrombus model in the rat femoral artery, by endothelial denudation using a photochemical reaction between rose bengal and green light (540 nm). Direct injury to vessels was not observed by this application and platelet-rich thrombus was produced by endothelial damage without alteration of medial smooth muscle cells (12)(13)(14). This model was adapted to mouse carotid arteries, and applied to the investigation of the role of fibrinolytic system components on thrombus and removal, using gene-inactivated mice with deficiencies of u-PA, t-PA or PAI-1.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported a simple and reproducible thrombus model in the rat femoral artery, by endothelial denudation using a photochemical reaction between rose bengal and green light (540 nm). Direct injury to vessels was not observed by this application and platelet-rich thrombus was produced by endothelial damage without alteration of medial smooth muscle cells (12)(13)(14). This model was adapted to mouse carotid arteries, and applied to the investigation of the role of fibrinolytic system components on thrombus and removal, using gene-inactivated mice with deficiencies of u-PA, t-PA or PAI-1.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that ATA is a useful prototype agent for inhibiting arterial thrombosis in vivo because ATA has been proven advantageous in the animal models of induced stenosis and vessel injury [15,19]. In the present study, we demonstrated a new antithrombotic effect of ATA: the dye compound ATA upregulated the surface thrombomodulin expression of endothelial cells and monocytes in a dose-dependent and time-dependent manner, and increased the mRNA level of endothelial thrombomodulin.…”
Section: Discussionmentioning
confidence: 69%
“…It is considered that ATA is a useful prototype agent for inhibiting arterial thrombosis in vivo because ATA has been proven to be advantageous in the animal models of induced stenosis and vessel injury [12,13]. ATA also inhibit endothelial apoptosis induced by oxidized low-density lipoprotein [14].…”
Section: Introductionmentioning
confidence: 99%